Factors influencing reading of IIUM today: a campus newspaper - Wok, Saodah; A.Manaf, Aini Maznina; Abu Shammala, Amani (University College of Islam Melaka, 2017)
IIUMToday is an official campus newspaper for the International Islamic University Malaysia (IIUM), operated by students under the jurisdiction of the Department of Communication, and was established on 1 May 2014. To assess the acceptance of the campus newspaper, a study was conducted to test the Cultivation Theory. The objectives of the study are: (1) to determine the levels for reasons of visiting the IIUMToday website, awareness of, perception on, attitude toward, and reading habit of IIUMToday among students in IIUM; (2) to test the relationships among the selected variables; and (3) to determine the predictors for reading habit of IIUMToday among students. The study uses a quantitative research design, employing a survey method with questionnaire as the research instrument for data collection. A total of 224 respondents were collected for the study. However, only 104 respondents were found to be readers of IIUMToday. Results show that there are moderate levels of reasons for visiting, awareness, perception, attitude and reading habit of IIUMToday by the students. The relationships among the variables concerned are significantly positive. In addition, all factors contribute to explaining the reading habit of IIUMToday except for attitude towards it.